"It Works for Me": Pseudotherapy Use is Associated With Trust in Their Efficacy Rather Than Belief in Their Scientific Validity - Gregorio Segovia; Gregorio Segovia; Belén Sanz-Barbero; Belén Sanz-Barbero; Belén Sanz-Barbero (Frontiers Media S.A., 2022)
Objectives: To identify how perceptions, attitudes, and beliefs towards pseudotherapies, health, medicine, and the public health system influence the pseudotherapy use in Spain.Methods: We carried out a cross-sectional study using the Survey of Social Perception of Science and Technology-2018 (5,200 interviews). Dependent variable: ever use of pseudotherapies. Covariables: attitude towards medicine, health and public health system; perceived health; assessment of the scientific character of homeopathy/acupuncture. The association was estimated using prevalence ratios obtained by Poisson regression models. The model was adjusted for age and socioeconomic variables.Results: Pseudotherapy use was higher in women (24.9%) than in men (14.2%) (p < 0.001). The probability of use in men (p < 0.001) and women (p < 0.001) increases with the belief in pseudotherapies' usefulness. Among men, a proactive attitude (reference: passive) towards medicine and health (RP:1.3), and a negative (reference: positive) assessment of the quality of the public health system increased use-probability (RP:1.2). For women, poor health perceived (referencie: good) increased likelihood of use (RP:1.2).Conclusion: Pseudotherapy use in Spain was associated with confidence in its usefulness irrespective of users' assessment of its scientific validity.